Pengembangan Bahan Ajar Berbasis Pendekatan STEM dalam Mata Pelajaran IPAS Kelas IV di SD/MI - R, Salma Fauziah; Carlian, Yayan; Mahmud, Muhammad Rifqi; Rahmaniar, Andinisa; Rohimah, Siti Maryam (Jurnal PGSD, 2025)
This research aims to develop STEM-based teaching materials for Natural and Social Sciences (IPAS) subjects for fourth-grade elementary school students. This development is carried out to meet the needs of 21st-century education. This research method used in this study is R&D (Research and Development) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model stages. This research uses qualitative and quantitative data. This research was conducted in the 4th grade of MI Baiturrahim. The data collection technique in this study used interviews with the 4th grade teacher, expert validation questionnaires including material, media, language, and STEM expert, as well as student response questionnaires after using STEM based teaching materials. The results of the validation test on the content feasibility aspect received a score of 87%, the graphic of 82%, the presentation of 79%, the language of 94%, and the STEM pf 100% and 97%. all validation test results from the 5 validators fall within the criteria of feasible. The score of all student responses after using STEM based teaching materials on a limited and broad scale received a score of 95% with very good criteria.